How Audiences Evaluate Motivation in Messages: Theory and Investigation. (Herald of Journalism, 2016)
This paper proposes a new theoretical construct of an aspect of communication that has apparently not been addressed by scholars: how, during the process of communication, the motivation of the message sender is evaluated. The authors developed a model of message processing that focuses on what they call “motivaluation”, or receiver interpretation of codes that suggest the motivation of the sender. Important factors are considered, such as previous attitudes, source, dimensions of motivation, verbal and nonverbal codes, sincerity, and changes throughout the process of communication interaction. One section of this methodology was applied to five Kazakhstani websites, as a pilot study to help refine and improve the concept, and the results suggest that the “motivaluation” approach has the potential of being useful for the study of all kinds of communication.
Keywords: motivation; message production; message interpretation; message evaluation.